Eventos extremos de precipitação sobre a região metropolitana de Belém durante o ano de 2021 - SILVA, Letícia Pereira da (2022)
Extreme precipitation events are increasingly present and more intense over the last years and they have concerned society with environmental and socioeconomic problems. This work aimed to study the daily extreme events in the metropolitan region of Belém during the year 2021. Six extreme events with daily rainfall exceeding the 98th percentile threshold (59.9 mm/day) were identified in the rainy season (February to May). The effect of these events on the diurnal cycle of meteorological variables was evaluated, with results indicating local impacts, mainly the intense and rapid decline in air temperature and the occurrence of gusts of wind at the entrance of the extreme event. The analysis of satellite images (GridSAT) showed that the extreme rainfall was caused by the passage of Lines of Instability or Convective Clusters, which were associated with other larger scale meteorological systems. Keywords: rainfall; extreme events; percentiles.